"Oh hell no, we don't talk to police": Insights on the lack of cooperation in police investigations of urban gun violence. Issue 3 (31st July 2019) - Brunson, Rod K.; Wade, Brian A.
Abstract : Research Summary: We conducted face‐to‐face interviews with 50 young Black men, residents of high‐crime neighborhoods in Brooklyn and the Bronx, individuals who had considerable knowledge about illegal gun markets and the resulting bloodshed. Our findings confirm that distressed milieus reliably fail to produce cooperative witnesses as a result of the cumulative impact of anti‐snitching edicts, fear of retaliation, legal cynicism, and high‐risk victims' normative views toward self‐help. Policy Implications: Disadvantaged communities of color typically have low fatal and nonfatal shooting clearance rates in part as a result of poor witness cooperation. Diminished clearance rates have also been shown to intensify minority residents' claims that officers do not care about keeping them or their neighborhoods safe. Respondents' accounts identify three overlapping areas instructive for informing public policy: (1) reducing gun violence so that high‐risk individuals live in objectively safer areas, (2) using intermediaries to launch grassroots campaigns countering pro‐violence and anti‐snitching norms, and (3) improving police–minority community relations.